Shaping a Suitable Leadership Style for Startup Business’ Founder: A Review - Ningrum, Rosidah Wulan (Universitas Muhammadiyah Magelang, 2025)
Effective leadership is critical for success and sustainability for the startups, particularly in dynamic and uncertain business environments. While various leadership styles have been studied in corporate settings, their influence on startup ecosystems remains less explored. This study examines the suitable leadership styles for startups founders, focusing their role in fostering innovation, adaptability, and long-term growth. This literature review study reveal three most fitting leadership styles for startups business founders and underscores the significance of integrating those leadership styles. A balanced leadership approach that blends transformational, sustainable, and resilient leadership appears most effective in driving startups success. This study recommends further empirical research to test the proposed model and explore the adaptive leadership strategies where leadership styles can be shifted based on certain conditions.